Analysis of Factors Affecting the Implementation of Uterine Exploration at the Third Stage of Labor - Bayu Irianti; Qanita Wulandara; Uly Artha Silalahi (EMBRIO: Jurnal Kebidanan, 2024)
Labor is one of the critical periods for women based on IDHS data up to 2020 shows that bleeding, hypertension in pregnancy, and infection are the causes of maternal death. Observation data was conducted in January-February 2022 at 5 Puskesmas in the city of Tasikmalaya, and it was found that 3 out of 5 women in labor underwent exploratory procedures during the third stage of labor because there were signs of retained placenta. The act of uterus exploration could be a portal of bacterial entry into the cavity and cause infection. This study aimed to look at the factors that affect the implementation of uterine exploration in the third stage of labor. The research method uses a sequential explanatory mix method to analyze the supporting factors for third-stage exploration actions by midwives. The research sample was 43 midwives. Quantitative results showed that there was no influence of characteristic factors on exploration actions (ρ more than 0.05), and there was no influence of self-efficacy on uterus exploration (ρ more than 0.05). Qualitative results showed that there were four main factors supporting exploration, such as visible signs of bleeding and weak contractions, ensuring that there were no remaining placentas and routine actions that were carried out. The research concludes that the exploratory action carried out is the midwife's accumulated experience, which results in the perception of dealing with cases of retained placenta in the third stage of labor, this makes the uterus exploration an additional action to anticipate problems.